UPAYA GURU DALAM IDENTIFIKASI SISWA DISLEKSIA - Syifa Qurrota A’yun; Eva Latipah (Universitas Pahlawan Tuanku Tambusai, 2022)
In the learning process at school there are several obstacles including many students who show symptoms of not being able to achieve learning outcomes as expected. Problems with learning disorders are often found, one of which is reading difficulties. Whereas one of the success of students' learning in participating in teaching and learning activities at school is determined by their ability to read, for that the teacher plays a major role in improving students' reading skills. The purpose of this study was to analyze the identification and treatment carried out by teachers for children with reading difficulties (dyslexia). The approach used a qualitative descriptive case study. Respondents in this study were the principal, grade 2 teacher, and students in grade 2 elementary school who had reading difficulties. Interview, observation and documentation techniques were used in collecting data in this study and analyzed using data reduction, then presenting the data and then concluded. The results of this study are dyslexia can be identified early on with tests conducted at the beginning of school enrollment and then there is special treatment, so that teachers can easily make efforts or provide assistance according to the needs they need, namely by providing special guidance. In addition to identification, there are also efforts that teachers can make in dealing with dyslexic children during online learning, namely by regularly communicating with teachers so that they know the development or abilities of children at school and discuss the child's condition with parents at home in order to find the best way to help children succeed in school. homeschooling. Keywords: Identification, Teachers, Students with Dyslexia